2019
DOI: 10.5194/acp-19-2861-2019
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of silicon in atmospheric aerosol secondary formation: a new conservative tracer for aerosol chemistry

Abstract: Abstract. Aerosol particles are ubiquitous in the atmosphere and affect the quality of human life through their climatic and health effects. The formation and growth of aerosol particles involve extremely complex reactions and processes. Due to limited research tools, the sources and chemistry of aerosols are still not fully understood, and until now have normally been investigated by using chemical species of secondary aerosols (e.g., NH4+, NO3-, SO42-, SOC) as tracers. Here we investigated the role of silico… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…After their emission into the environment, in particular, the atmosphere, carbon-or silica-based particulate matter first meet and interact with various airborne pollutants to suffer complex transformation to form the secondary aerosol particles. 37 The initial physicochemical properties of the carbon and silica cores are among the most important factors that determine the particle−pollutant interactions but have long been ignored. In the present study, carbon-and silicabased model PM 2.5 particles were synthesized and applied to explore how the core materials of carbon and silica affected the loadings of various pollutants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After their emission into the environment, in particular, the atmosphere, carbon-or silica-based particulate matter first meet and interact with various airborne pollutants to suffer complex transformation to form the secondary aerosol particles. 37 The initial physicochemical properties of the carbon and silica cores are among the most important factors that determine the particle−pollutant interactions but have long been ignored. In the present study, carbon-and silicabased model PM 2.5 particles were synthesized and applied to explore how the core materials of carbon and silica affected the loadings of various pollutants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The data points from April 6 were quite different from others, resulting from the combination of a high level of O 3 and the small number of residual pollutants in the air, which are caused by seasonal characteristics and fossil fuel combustion in motor vehicles, respectively, considering sampling time and position. Compared with Table , Si + and SiH + appeared in Table , which may correspond to substances in soil, cement, or lime . Beijing has frequent sandstorms in spring, during which the sand and dust from the north contribute greatly to the PM 2.5 in the spring in Beijing.…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Even though the concentrations of SO 2 and NO 2 on that day are relatively low, they could still make a great contribution to particulate mat- Table 4, which may correspond to substances in soil, cement, or lime. 23,25,44 Beijing has frequent sandstorms in spring, during which the sand and dust from the north contribute greatly to the PM 2.5 in the spring in Beijing. The dust can stay in the near-surface atmosphere for a long time so the silicon can be found even in the good air quality days in spring.…”
Section: Pca Of Aerosol Particle From Four Seasonsmentioning
confidence: 99%
“…In our previous studies, we have shown that different primary sources of PM 2.5 (e.g., coal burning, industrial emission, dusts, and vehicle emission) have distinguishable Si isotopic fingerprints, thus enabling the direct tracing of primary sources of PM 2.5 by the Si isotopic composition . Furthermore, as a relatively inert element, Si content in PM 2.5 is predominantly emitted from primary sources and the total mass of Si in PM 2.5 is unlikely to be affected by the secondary aerosol formation process . Thus, the secondary aerosol formation can cause a dilution of the Si abundance in PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the secondary aerosol formation can cause a dilution of the Si abundance in PM 2.5 . On the basis of such an Si-dilution effect, it is possible to rapidly estimate the contribution of secondary aerosols to PM 2.5 . These studies have revealed the great potentials of Si as a new tracer for PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%